Effect of human lactoferrin on Candida albicans infection and host response interactions in experimental oral candidiasis in mice. (May 2022) - Pawar, Siddhi; Markowitz, Kenneth; Velliyagounder, Kabilan
Abstract: Objectives: To determine the effect of human lactoferrin (hLF) in experimental oral candidiasis and examine the host-pathogen interactions in a mouse model . Design: Experimental groups comprised of 4–6-week-old wild type (C57BL/6J) or lactoferrin knockout ( ltf -/- ) immunosuppressed mice. Six mice in each group were inoculated with C. albicans or sham infection by swabbing the oral cavity. To determine the effect of hLF on infection and host response, we added hLF (0.5 g/kg/day) to the drinking water. Candida and mice RNA were isolated from gingival tissue and analyzed by qRT-PCR for virulence genes and host expression of inflammatory mediators. Results: Administration of hLF significantly reduced the C. albicans CFUs in both WT and ltf -/- mice (P < .001). Examination of the oral cavity of ltf -/- I mice revealed lesions characterized by white patches and inflammation when compared to WTI mice. Several Candida virulence genes (als, ece, efg, sap) were significantly downregulated on administration of hLF to WTI and ltf -/- I mice (P < .001). The WTI+hLF mice had significantly increased expression of toll-like receptors (TLRs) compared to other group. We observed that hLF increased expression of interleukins, IL-1β, IL-6, IL-12, IL-17, tumor necrosis factor alpha (TNF-α), transforming growth factor beta (TGF-β), inducible nitric oxide synthase (iNOS) and myeloperoxidase (MPO) compared to untreated gingival tissue. Conclusion: Our study highlights the protective effect of hLF against oral C. albicans infection by its actions on both microbial and host factors. HLF may be of therapeutic value to protect against oral candidiasis. Highlights: Human lactoferrin (hLF) limits the extent of oral tissue infection by C. albicans . Administration of hLF limits oral infection in animals lacking endogenous lactoferrin. HLF modulates key aspects of the host response associated with inflammation. HLF down regulates C. albicans virulence factors associated with oral tissue invasion.